2019
DOI: 10.3390/antiox9010020
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil and Nigella sativa Oil Produced in Central Italy: A Comparison of the Nutrigenomic Effects of Two Mediterranean Oils in a Low-Grade Inflammation Model

Abstract: Extra virgin olive (EVO) oil and Nigella sativa (NG) oil are two well-known Mediterranean foods whose consumption has been associated with beneficial effects on human health. This study investigates the nutrigenomic properties of two high quality EVO and NG oils in an in vitro model of low-grade inflammation of human macrophages (THP-1 cells). The aim was to assess whether these healthy foods could modulate inflammation through antioxidant and epigenetic mechanisms. When THP-1 cells were co-exposed to both lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In addition to polyphenols, the anti-inflammatory role of other dietary factors and specific functional foods has also been assessed in different experimental models. In this regard, extra virgin olive oil (EVOO) and Nigella sativa oil displayed anti-inflammatory activities in lipopolysaccharide (LPS)-exposed human macrophages through epigenetic mechanisms [38]. In this study, the administration of both oils reverted the altered expressions of DNMT3A and HDAC1 to normal levels under inflammatory conditions, with an additional role of EVOO in the reduction of global methylation.…”
Section: Nutrition/dietary Bioactive Compoundsmentioning
confidence: 77%
“…In addition to polyphenols, the anti-inflammatory role of other dietary factors and specific functional foods has also been assessed in different experimental models. In this regard, extra virgin olive oil (EVOO) and Nigella sativa oil displayed anti-inflammatory activities in lipopolysaccharide (LPS)-exposed human macrophages through epigenetic mechanisms [38]. In this study, the administration of both oils reverted the altered expressions of DNMT3A and HDAC1 to normal levels under inflammatory conditions, with an additional role of EVOO in the reduction of global methylation.…”
Section: Nutrition/dietary Bioactive Compoundsmentioning
confidence: 77%
“…Therefore, at the end of the selection process, 43 studies were included in the systematic review ( Figure 1 ). Among them, 18 reported data on miRNAs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], 10 on DNA methylation [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], 9 on histone modification [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], 2 on histone modification/DNA methylation [ 58 , 59 ], 2 on miRNAs/DNA methylation [ 60 , 61 ] one each on miRNA/histone modification [ 62 ] and on miRNA/histone modification/DNA methylation [ 63 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 15 selected studies investigating the effects of olive oil and its phenolic compounds on DNA methylation are shown in Table S2 . Five studies reported data in vitro on cell systems [ 46 , 53 , 59 , 60 , 63 ], 8 studies showed results on animal models [ 40 , 41 , 42 , 43 , 48 , 58 , 60 , 61 ] and 3 studies reported results on human trials [ 39 , 45 , 47 ]. Eleven studies were carried out with olive oil [ 39 , 40 , 41 , 42 , 43 , 45 , 47 , 58 , 59 , 60 , 61 ], 2 articles reported data on oleacein [ 46 , 63 ], one study each investigated the effect of hydroxytyrosol [ 48 ] and of an extract obtained from Olea europaea leaves [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline of membrane fluidity negatively interferes with the membrane protein dynamicity and finally, influences protein functions. Lower fluidity can depend on the fatty acid composition, the oxidative process at lipid or protein level, and metabolic regulation [30,46]. Lipid composition varies according to the diet: a diet rich in mono-polyunsaturated fatty acids (i.e., extra virgin olive oil (EVOO), seed) modulates bilayer composition toward a more fluid state of lipids, compared to a saturated fatty acid diet (i.e., meat, cheese).…”
Section: Discussionmentioning
confidence: 99%